METYRAPONE AS A BRIDGING THERAPY IN FLORID CUSHING’S DISEASE PATIENT PRIOR TO PITUITARY ADENOMECTOMY - MY, Muhamad Shafiq; WA, Siti Sanaa; MA, Masliza Hanuni; MM, Nur Hidayah (Journal of the ASEAN Federation of Endocrine Societies, 2023)
INTRODUCTION/BACKGROUND Florid Cushing’s disease gives rise to high morbidity and mortality due to its metabolic abnormalities and the risk of infection. Preoperative medical therapy with steroidogenesis inhibitors such as metyrapone, an 11βhydroxylase inhibitor, may be considered if surgery is delayed or rapid reduction of cortisol is needed in patients with severe Cushing's who have potentially life-threatening metabolic, infectious or thromboembolic cardiovascular complications. CASE We describe a 31-year-old female who presented with lethargy and a short history of body acne, proximal muscle weakness, and hair loss for a month. She had missed her menses for two months. Upon examination, she was hypertensive (BP 190/112 mmHg), BMI was 26 kg/m2. She had hirsutism, hyperpigmentation over her lips, knuckles, and nail folds, facial and body acnes, alopecia, proximal muscle weakness, acanthosis nigricans, dorsocervical and supraclavicular fat pads and purplish striae over her abdomen. Initial blood results revealed severe hypokalaemia (1.9 mmol/l), metabolic alkalosis (HCO3 41.3 mmol/l), HbA1c 9.2% and transaminitis (ALT 324 U/L, AST 130 U/L) which precludes initiation of ketoconazole. ODST was not suppressed with a cortisol level of 1406 nmol/l, and HDDST showed 50% reduction of cortisol from baseline (baseline 1059 nmol/l, post 530 nmol/l). 24-hour urine cortisol was markedly elevated at 10,352 nmol/day. ACTH level was raised at 38.4 pmol/L. Pituitary MRI demonstrated a bulky left pituitary gland measuring 0.6 cm x 0.7 cm x 0.4 cm. CT TAP showed no evidence of a suspicious lesion/mass suggestive of ectopic Cushing's. She initially required high doses of basal-bolus insulin and potassium replacement together with four antihypertensives. We commenced her on Metyrapone 250 mg TDS and this was titrated to 500 mg TDS based on serial cortisol levels. We attained a cortisol level of 531 nmol/l with better control of her blood pressure and glucose level prior to pituitary adenomectomy with TSS. CONCLUSION This case illustrates the effectiveness of metyrapone in achieving normal biochemical clinical parameters preoperatively before undergoing pituitary surgery.